2022
DOI: 10.3389/fvets.2022.930450
|View full text |Cite
|
Sign up to set email alerts
|

Internet Survey Evaluation of Iliopsoas Injury in Dogs Participating in Agility Competitions

Abstract: ObjectiveTo describe risk factors associated with demographics, training, and competition for iliopsoas injury in dogs participating in agility competitions, as well as describe owner reported treatment and return to sport following injury.ProceduresAn internet-based survey of agility handlers collected risk factor data for dogs participating in agility. Owners were asked questions about demographics, training, and competition as well as injury treatment and recovery if applicable. Associations between variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To account for this, IP was calculated to present the rate of injury on a substrate relative to the proportion of dogs training on that substrate. IP has not been utilized in other studies evaluating the proportion of injuries sustained on different surfaces in agility dogs ( 3 , 4 , 16 ), which may skew results toward more common surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To account for this, IP was calculated to present the rate of injury on a substrate relative to the proportion of dogs training on that substrate. IP has not been utilized in other studies evaluating the proportion of injuries sustained on different surfaces in agility dogs ( 3 , 4 , 16 ), which may skew results toward more common surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that natural grass, dirt, and artificial turf may provide improved performance and reduced risk of injury. In a recent evaluation of common surfaces in agility competition, Fry et al ( 16 ) reported that dogs who had ever competed on dirt or artificial turf were more likely to have reported an iliopsoas injury, compared to dogs with no history on that surface. However, that study did not evaluate the substrate in use at the time the injury was sustained, only the dogs' history of prior substrate use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of those studies and the current study are remarkably similar, with the identification of shoulder, back, iliopsoas muscle, and digit injuries as the most common sites of injury. Despite this consistent finding, there is little research that has specifically investigated the nature, cause, treatment, or prognosis related to shoulder, back, or iliopsoas injuries in agility dogs ( 23 ). The data must also be interpreted with some caution because all reports have relied exclusively on owner-provided information regarding the anatomic location or diagnosis of the injury rather than review of veterinary medical records.…”
Section: Discussionmentioning
confidence: 99%